ESCALATING THE SPIRITUAL EXPERIENCE OF GURU SEKUMPUL TOMB'S RELIGIOUS TOURISM THROUGH MARKETING COMMUNICATION STRATEGY - Armiah, Armiah; Khaliq, Restu; Sagir, Akhmad; Gusriani, Raden Yani; Gazali H B, Ahmad (Khazanah: Jurnal Studi Islam dan Humaniora, 2023)
Religious tourism holds a significant position in the global tourism industry, attracting visitors to culturally and spiritually significant pilgrimage sites. Indonesia, ranked second in The Global Travel Muslim Index 2022, has witnessed a rise in Muslim tourists exploring religious destinations. Ensuring the sustainability of religious tourism and enhancing the spiritual pilgrimage experience necessitates critical thinking, innovative approaches, and effective communication strategies. Promotion through social media is crucial for marketing religious tourism destinations. However, challenges persist in Indonesia's tourist development due to the absence of an integrated marketing communication strategy. Research emphasizes the importance of communication strategies and the preservation of cultural and religious diversity for the sustainability of religious tourism. In South Kalimantan, despite the potential for religious tourism, the COVID-19 pandemic has led to a decline in visitor numbers. Employing a qualitative approach, including interviews and SWOT analysis, this study formulates a strategic communication plan for promoting the Guru Sekumpul Tomb. The strategy focuses on product packaging, nuanced marketing communication, a serene pilgrimage ambiance, and leveraging digital media platforms, along with collaboration with local stakeholders and optimal use of natural resources. Ultimately, integrating innovative knowledge and skills is crucial for the success and sustained viability of religious tourist sites, concurrently elevating the spiritual pilgrimage experience.